2019
DOI: 10.1111/jfpp.14232
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties, in vitro digestibility and structural attributes of okara‐enriched functional pasta

Abstract: Soy okara is a by‐product of soybean processing which offers immense potential to be incorporated into the diverse food products due to its high nutritional and biological significance. The current research aimed to examine the impact of varying soy okara contents (10%–50%) on physicochemical attributes, in vitro protein digestibility, and glycaemic index (GI) of microwave processed durum wheat semolina pasta. Total phenolic content and antioxidant activity improved when 50% of soy okara was added (158.37 ± 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 49 publications
4
55
0
2
Order By: Relevance
“…It has been stated that β‐glycosidic bonding is a main structural feature of immunostimulatory and antitumor effects. Kamble et al () also confirmed the existence of transmittance bands at 1,010, 1,529, 1,696, 2,362, 2,931, 3,635, 3,745, and 3,846 cm −1 regions in pasta formed with okara flour integration. The observed transmittance peak at 1,010 cm −1 may be correlated with the amorphous state of starch granules resulting from the C─O─ stretching vibration (Bashir & Aggarwal, ).…”
Section: Structural Characteristics Of Okaramentioning
confidence: 78%
See 4 more Smart Citations
“…It has been stated that β‐glycosidic bonding is a main structural feature of immunostimulatory and antitumor effects. Kamble et al () also confirmed the existence of transmittance bands at 1,010, 1,529, 1,696, 2,362, 2,931, 3,635, 3,745, and 3,846 cm −1 regions in pasta formed with okara flour integration. The observed transmittance peak at 1,010 cm −1 may be correlated with the amorphous state of starch granules resulting from the C─O─ stretching vibration (Bashir & Aggarwal, ).…”
Section: Structural Characteristics Of Okaramentioning
confidence: 78%
“…The structural study of okara flour was previously investigated using various techniques, including scanning electron microscopy (SEM; Porcel et al, ; Voss et al, ; Santos et al, ) and Fourier transform infrared (FTIR) spectroscopy (Kamble et al, ; Li et al, ; Quintana, Gerbino, & Gómez‐Zavaglia, ). SEM is a useful technique for determining the microstructure of food products by evaluating the arrangement of starch granules within the protein matrix (Kamble et al, ). Santos et al () conducted a study to examine the microstructure of okara flour particles by means of an SEM (Figure ).…”
Section: Structural Characteristics Of Okaramentioning
confidence: 99%
See 3 more Smart Citations